Prognostic Role of High Sensitivity C-Reactive Protein in Patients With Acute Myocardial Infarction - Zhang, Xiaoyuan; Wang, Shanjie; Fang, Shaohong; Yu, Bo (Frontiers in Cardiovascular Medicine, 2021)
Background: High sensitivity CRP (hs-CRP) has attracted intense interest in risk assessment. We aimed to explore its prognostic value in patients with acute myocardial infarction (AMI). Methods and Results: We enrolled 4,504 consecutive AMI patients in this prospective cohort study. The associations between hs-CRP levels with the incidence of in-hospital HF was evaluated by logistic regression analysis. The association between hs-CRP levels and the cumulative incidence of HF after hospitalization were evaluated by Fine-Gray proportional sub-distribution hazards models, accounting for death without HF as competing risk. Cox proportional hazards regression models were constructed to estimate the association between hs-CRP levels and the risk of all-cause mortality. Over a median follow-up of 1 year, 1,112 (24.7%) patients developed in-hospital HF, 571 (18.9%) patients developed HF post-discharge and 262 (8.2%) patients died. In the fully adjusted model, the risk of in-hospital heart failure (HF) [95% confidence intervals (CI)] among those patients with hs-CRP values in quartile 3 (Q3) and Q4 were 1.36 (1.05–1.77) and 1.41 (1.07–1.85) times as high as the risk among patients in Q1 (p trend < 0.001). Patients with hs-CRP values in Q3 and Q4 had 1.33 (1.00–1.76) and 1.80 times (1.37–2.36) as high as the risk of HF post-discharge compared with patients in Q1 respectively (p trend < 0.001). Patients with hs-CRP values in Q3 and Q4 had 1.74 (1.08–2.82) and 2.42 times (1.52–3.87) as high as the risk of death compared with patients in Q1 respectively (p trend < 0.001). Conclusions: Hs-CRP was found to be associated with the incidence of in-hospital HF, HF post-discharge and all-cause mortality in patients with AMI.